The Role of Digital Accounting for SMEs in Facing Business Challenges in the Digital Era - Badria, Nuril; Hasanah, Naimatul (Profesional Muda Cendekia Publishing, 2024)
Research Aims: This research aims to analyze the role of digital accounting in increasing operational efficiency and to examine how digital accounting supports MSMEs in adapting to the challenges of the digital era. Design/methodology/approach: The research employed direct observation and interviews with MSMEs in Malang, encompassing various business types, ages, and education levels. This approach provided a comprehensive understanding of the significance of digital accounting for MSMEs in navigating the business environment in the digital era. Additionally, the researchers conducted digital accounting training for MSMEs to further enhance their understanding. Research Findings: The findings indicate that the implementation of digital accounting offers significant advantages for MSMEs, particularly in improving operational efficiency and enabling quicker, more accurate business decisions. These benefits enhance the competitiveness of MSMEs in the digital era. However, the study also identified key challenges, such as the costs associated with digital accounting implementation and the limited understanding and knowledge among MSMEs regarding its use. Theoretical Contribution/Originality: This study adds to the growing body of literature by emphasizing the critical role of digital accounting in enhancing MSME performance in the digital business landscape. It highlights the need for comprehensive training and support to overcome the barriers associated with digital accounting adoption in MSMEs, offering practical insights for both academia and practitioners.